A suplência no nível médio de ensino pelo desempenho acadêmico em cursos de graduação: um estudo de trajetórias escolares - Silva, Ani Martins da (2007)
This research focuses on social and school influences manifested in the performances of graduating students from different courses of the university-source and who are similar to each other for having concluded their high school studies by means of replacement courses. The theoretical grounds can be found in the Sociology of Education area and refer to the scientific findings of Pierre Bourdieu, for whom the school performance cannot be satisfactorily studied when apart from the social origins of the student. It is the cultural capital of family origin that defines the path of the school trajectories of his descendants. That theoretical proposition grounded the development of the following hypothesis: the academic performance of graduating courses students, who have concluded the high school studies in the EJA modality, depends much more on the cultural capital of the student s origin, linked to his social class status, than on the quality of the replacement course he has attended. The methodology is qualified by data collection, mainly interviews - which, submitted to analyses, aimed at reaching the suggested aims: a) to understand the school trajectory that is being build, as an experience of success or failure updating, in the graduation course ; b) to get to know the personal strategies employed by the graduating students in order to face the replacement course demands, as well as the graduation course demands, with the purpose of understanding and analyzing the relationships established with the school institution and the learning intermediated by that institution; c) to get to know and analyze the meaning given by the graduating student to the replacement course and his previous and current school trajectory. It was evidenced, in the flow of the analyses of the school trajectories, that they are qualified as success or failure stories regardless of the cultural capital of family origin. Therefore, the hypothesis was partially evidenced. In regards to the strategies employed by each one of them, it was seen that they are applied in a reverse proportion: the lower the cultural capital of origin, the greater the number and the intensity of the strategies. The meaning given to the replacement course: was relevant for a quicker access to university; certifies the agent for the insertion in a more qualified position, or enables the conciliation of the professional activity with the replacement course